The Impact of Big Data Analytics on Production Optimization and Decision-Making in Industry - Azwan Khoirul Ihsan; Hidayatul Ikhsan (YCMM, 2025)
This study aims to examine the impact of Big Data Analytics (BDA) on production optimization and decision-making in the industrial sector. A Systematic Literature Review (SLR) method was applied, reviewing scientific articles published between 2018 and 2023 from reputable databases such as Scopus, ScienceDirect, and IEEE Xplore. The selection process was conducted in stages using predefined inclusion and exclusion criteria, resulting in six key articles for further analysis. The findings indicate that BDA significantly contributes to improving production efficiency, reducing operational costs, and enhancing the speed and quality of data-driven decision-making. However, several challenges remain in the implementation of BDA, particularly in terms of technological infrastructure, human resource readiness, and system integration. This study provides a comprehensive understanding of the strategic importance of BDA adoption in building industrial competitiveness in the digital era.